2022
DOI: 10.3389/fonc.2022.958065
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated detection and localization of clinically significant prostate cancer on MR images using a cascaded convolutional neural network

Abstract: PurposeTo develop a cascaded deep learning model trained with apparent diffusion coefficient (ADC) and T2-weighted imaging (T2WI) for fully automated detection and localization of clinically significant prostate cancer (csPCa).MethodsThis retrospective study included 347 consecutive patients (235 csPCa, 112 non-csPCa) with high-quality prostate MRI data, which were randomly selected for training, validation, and testing. The ground truth was obtained using manual csPCa lesion segmentation, according to patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The commercially available software provided at https://fuse-ai.de/prostatecarcinoma-ai has a comparable level of reliability to that of radiologists in detecting carcinomas, with a patient-level sensitivity of 0.86, which, in contrast, is inferior to our model’s sensitivity value of 0.94. Several researchers ( 18 , 26 , 29 ) have sought to evaluate the efficacy of the U-Net network for PCa detection at various levels, including the lesion, sextant, and patient levels. However, these studies did not examine the effect of different cancer foci on the diagnostic efficiency of the models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commercially available software provided at https://fuse-ai.de/prostatecarcinoma-ai has a comparable level of reliability to that of radiologists in detecting carcinomas, with a patient-level sensitivity of 0.86, which, in contrast, is inferior to our model’s sensitivity value of 0.94. Several researchers ( 18 , 26 , 29 ) have sought to evaluate the efficacy of the U-Net network for PCa detection at various levels, including the lesion, sextant, and patient levels. However, these studies did not examine the effect of different cancer foci on the diagnostic efficiency of the models.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, their proposed co-trained CNNs were fed with pairs of aligned ADC and T2WI squares. Expanding on this work, Wang et al ( 35 ) and Zhu et al ( 29 ) adapted the workflow to create an end-to-end trainable deep neural network comprising two sub-networks. The first sub-network was responsible for prostate detection and ADC-T2WI registration, while the second sub-network was a dual-path multimodal CNN that generated a classification score for csPCa and non-csPCa.…”
Section: Discussionmentioning
confidence: 99%
“…Using artificial intelligence (AI) methods, such as deep learning (DL), can improve the detection and classification of PCa on mpMRI images [ 4 ]. Previous studies have shown that AI can improve the accuracy and efficiency of PCa detection on mpMRI images by automatically detecting and segmenting suspicious areas for further evaluation by a radiologist [ 5 ]. Several recent studies have indicated the potential of AI in predicting tumor invasiveness of biopsy pathology [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%